1993
DOI: 10.4315/0362-028x-56.11.963
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Molds on Cheese Treated with Heat or Liquid Smoke

Abstract: Liquid smoke and heat treatments were evaluated for their potential use to inhibit growth of Aspergillus oryzae, Penicillium camemberti, and Penicillium roqueforti on Cheddar cheese. A. oryzae had a longer lag period and P. roqueforti grew faster radially on cheese heated at 42°C for 1 h than on unheated cheese. Mold growth on cheese heated at 24 and 33°C for 1 h was not significantly different from that on the unheated control. Liquid smoke applied to the surface of cheese totally inhibited growth of A. oryza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…(2007) demonstrated that an olive oil treatment on surface of Canestrato Pugliese cheese was not efficient to inhibit the mould growth during 100 days of ripening. In fact, this result is in accordance with previous studies, where it has been demonstrated that if a rind has not yet formed, oil triglycerides act as substrates that promote mould growth, while, when rind is present on the cheese surface, olive oil can act as an oxygen barrier, inhibiting fungal growth (Wendorff et al. 1993; Wendorff and Wee 1997).…”
Section: Resultssupporting
confidence: 92%
“…(2007) demonstrated that an olive oil treatment on surface of Canestrato Pugliese cheese was not efficient to inhibit the mould growth during 100 days of ripening. In fact, this result is in accordance with previous studies, where it has been demonstrated that if a rind has not yet formed, oil triglycerides act as substrates that promote mould growth, while, when rind is present on the cheese surface, olive oil can act as an oxygen barrier, inhibiting fungal growth (Wendorff et al. 1993; Wendorff and Wee 1997).…”
Section: Resultssupporting
confidence: 92%
“…On the contrary, cheese with olive oil treatment (O samples) showed the highest mould count and the highest number of identified species. This result is in accordance with previous studies, where it has been demonstrated that if a rind has not yet formed, oil triglycerides act as substrates that promote mould growth, while, when rind is present on the cheese surface, olive oil can act as an oxygen barrier, inhibiting fungal growth (Wendorff et al, 1993;Wendorff & Wee, 1997). Some fungal species, e.g., Aspergillus flavus and Penicillium commune, were found on the surface of all samples examined.…”
Section: Resultssupporting
confidence: 92%
“…Wendorff, Riha, and Muehlenkamp (1993) showed that it is possible to reduce fungal growth by smearing the cheese surface with liquid smoke. Another way to inhibit the growth of undesirable moulds is to induce (e.g., by inoculation) the growth of non-toxic antagonist moulds (Salvadori Del Prato, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Wendorff et al . () found that the phenolic components of wood smoke provided the primary antifungal properties in smoked cheese.…”
Section: Discussionmentioning
confidence: 99%